Audit committee effectiveness and internal audit: an empirical investigation with audit quality - Puat Nelson, Sherliza; Mat Yasin, Siti Fatimah (2012)
Increased concerns regarding corporate accountability in various developed nations have been associated with the need for effective audit committee and internal control systems. This is due to large corporate collapses which have demonstrated problems with the quality of financial reporting and auditing. This study examines the nature and extent of the relationship between audit committee characteristics and internal audit function characteristics with audit quality whereby audit fee is used as a proxy for audit quality. The corporate governance characteristics included in this study are audit committee expertise, frequency of audit committee meetings, structure of internal audit function and size of internal audit function. This study formulated six hypotheses that guided the analysis and using publicly available information of 200 Malaysian public listed companies for the financial year end 2009 and 2010 each. This study provides recent evidence of a positive relationship between audit quality and two audit committee characteristics: audit committee with postgraduate qualification and frequency of audit committee meeting. Further, a positive relationship is found between audit quality and internal audit function characteristic, which is size of internal audit function. Apart from contributing to the literature on corporate governance and audit quality, this study may serve as an input for the regulator to encourage strict enforcement for Malaysian-listed companies to incorporate corporate governance practices especially on audit committee composition and internal audit function. Finally, it highlights the call for continuous education for directors, to become more resourceful in order to improve relationship with auditors.